Work stress & sleep quality as factors of hypertension in Labuhan Deli - Selviyani Harefa; Damaria Waruwu; Andry Simanullang; Putri Yunita Pane (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Hypertension is a non-communicable disease with high prevalence that constitutes a leading cause of morbidity and premature mortality worldwide. Work stress and poor sleep quality are presumed to contribute to blood pressure elevation among working populations. This study aimed to analyze the relationship between work stress and sleep quality with hypertension incidence among workers in the Labuhan Deli Public Health Center working area. Methods: An analytical cross-sectional design with a quantitative approach was employed. The sample comprised 98 respondents selected through purposive sampling based on inclusion and exclusion criteria. Data collection utilized the Job Stress Questionnaire (JSQ) to measure work stress, the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, and sphygmomanometer measurements for blood pressure determination. Data analysis employed the Chi-Square test with a significance level of α=0.05. Results: Results demonstrated that the majority of respondents experienced high work stress (42.9%), poor sleep quality (63.3%), and hypertension (53.1%). Significant associations were identified between work stress and hypertension incidence (p=0.019) and between sleep quality and hypertension incidence (p=0.019). Workers with high work stress exhibited a greater proportion of hypertension (66.7%) compared to those with mild work stress (27.8%). Similarly, workers with poor sleep quality demonstrated a higher hypertension proportion (62.9%) compared to those with good sleep quality (36.1%). Conclusion: It is concluded that work stress and sleep quality are significantly associated with hypertension incidence among workers. Stress management and sleep quality improvement efforts need to be integrated into occupational health programs for hypertension prevention.